Uncontrolled eating is associated with reduced executive functioning. Issue 3 (7th May 2014) - Calvo, D.; Galioto, R.; Gunstad, J.; Spitznagel, M. B.
Summary Accumulating evidence indicates obesity is associated with reduced cognitive functioning, particularly attention and executive function, as well as maladaptive eating behaviour such as uncontrolled eating. The current study examined relationships between eating patterns and attention/executive function test performance in lean and obese individuals. Sixty‐two (32 lean, 30 obese) healthy young adults (21.13 ± 2.31 years; 56.5% female) completed the abbreviated Three‐Factor Eating Questionnaire (TFEQ‐R18) to assess eating patterns, including uncontrolled eating, cognitive restraint, and emotional eating. The Go/No‐Go (GNG), Running Memory Continuous Performance Test (RCMPT) and Standard Continuous Performance Test from the Automated Neuropsychological Assessment Metrics‐4 were administered as measures of executive functioning and attention. An independent samples t‐test revealed greater report of uncontrolled eating in obese compared with lean participants (t[60] = −2.174, P < 0.05; d = −0.55) but no differences in cognitive restraint or emotional eating. Multivariate analysis of variance revealed cognitive differences between lean and obese groups (F[6, 54] = 3.86, P < 0.005; λ = 0.70; ηp2 = 0.30), which were driven by GNG reaction time (F[1, 59] = 8.36, P < 0.01, d = 0.74). Pearson bivariate correlations revealed a positive correlation between uncontrolled eating and reaction time on GNG (r = 0.343, P < 0.05) and RMCPT (r = 0.267, P < 0.05) in all participants. Relative to lean participants, obese individuals reported higher levels of uncontrolled eating and exhibited slower performance on a task of inhibitory control. In the full sample, greater self‐reported dyscontrol in eating behaviour was related to slower inhibitory control and working memory. Results support a link between executive function and control of eating behaviour. Obese individuals may be more vulnerable to difficulties in these domains relative to those who are lean.